I Take Care of My Kids - Michael Smith; Thomas Noeller (Association of American Medical Colleges, 2011)
Abstract This human patient simulator case involves an infant sustaining nonaccidental trauma (child abuse) with deceit from the patient's caretakers. Along with the neurological and airway issues that can be introduced, the case allows for debriefing and discussion of state legal requirements for child abuse and the use of standardized actors to act as belligerent parents. This simulation deals with something most doctors dread encountering but have a medical, legal, and moral obligation to identify and treat. The simulation, in combination with a high-fidelity mannequin and live actors, provides for a rich learning environment that can touch on all of the ACGME core competencies. The simulation lasts 45-60 minutes. We rotated approximately 39 residents through the scenario. One faculty member and programmer were required per scenario. Each scenario was then video debriefed. The overall case played out very well. We have used some variations of the case for flight nurses where the parents refuse transport, which opens up teaching opportunities on medical responsibility, state laws, and child abuse in general.